Transplantation in Highly Sensitised Patients Treated with Intravenous Immunoglobulin and Rituximab - Ferreira, AC (2010)
Renal transplant in highly sensitised patients is associated with increased morbidity. The aim of this retrospective study was to evaluate the clinical evolution of 30 highly sensitised deceased donor kidney transplants and the influence of different timing of B cell directed treatment and its importance in the outcome of these patients. All recipients had negative complement dependent lymphocytotoxicity cytotoxic T cell crossmatch and no identified anti human leucocyte antigen class I donor specific antibodies. T cell flow crossmatch was performed within 24h of transplantation with serum obtained pretransplant (historic, recent or baseline). Posttransplant flow crossmatch were performed prospectively starting on the 3rd posttransplantation day. The immunosuppressive regime included thymoglobulin, tacrolimus, mycofenolate mofetil and steroids. Positive flow crossmatch occurred in 20/29 patients by the 3rd posttransplantation day, and in 17/27 patients after the 3rd posttransplantation day. All patients were started on intravenous immunoglobulin before transplantation: in nine patients (group A) at 400mg/kg/day for five days; in the remaining 21 patients (group B), as a continued infusion of 2g/kg during 48h. In group A, Rituximab was added only in the presence of antibody mediated rejection; in group B, introduced on the 3rd posttransplantation day whenever a positive flow crossmatch (with serum obtained pre or posttransplant) was reported. Antibody mediated rejection was observed in 44.4% of patients in group A, and 19% of those in group B. Mean follow-up was 12.2±5.5 months. Overall allograft survival was 76.6%, 81% in group B, and 66.6% in group A. At last follow up, mean serum creatinine was 1.3±0.6 mg/dl. Renal transplantation with pretransplant positive flow crossmatch is highly associated with antibody mediated rejection, despite introduction of intravenous immunoglobulin pretransplantation. However high dose intravenous immunoglobulin for 48h plus Rituximab by the 3rd posttransplantation day reduce the incidence of antibody mediated rejection by more than 50% and allowed for allograft survival of 81% at one year, with an excellent renal function.